2021
DOI: 10.1177/21582440211032176
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Skits: Reshaping the Entertainment Experience of Broadcast Audience

Abstract: The emergence of social media has produced diverse changes for broadcast media in the discharge of their entertainment function. While the uses and gratification theory identifies entertainment as one of the needs that motivate the audience to use the media, the technological determinism theory argues that the nature and strength of interaction in the society change as new media technologies evolve. This study is a descriptive and predictive discourse on how social media skits are reshaping audience consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Also in line is the study of Markom et al, (2019), who revealed that due to the rate of insecurity in the southeast region of Nigeria, people now take extra measures to protect themselves from harm. (Ojomo & Sodeinde, 2021) revealed that exposure to social media messages on insecurity can influence residents' perceptions of and attitudes towards insecurity measures. This result is consistent with the technological determinism theory, which holds that technology can influence social change and human interaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also in line is the study of Markom et al, (2019), who revealed that due to the rate of insecurity in the southeast region of Nigeria, people now take extra measures to protect themselves from harm. (Ojomo & Sodeinde, 2021) revealed that exposure to social media messages on insecurity can influence residents' perceptions of and attitudes towards insecurity measures. This result is consistent with the technological determinism theory, which holds that technology can influence social change and human interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Citizen journalists have evolved as a result of how communication has altered due to technological advancement. Around the world, news reporting has become more democratic, and social media are now used as channels for communication and impact (Ojomo & Sodeinde, 2021). The presence of new media technology has made the spread of information on security issues easy and prompt.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…A skit is a short performance in which the actors make fun of people, events and types literature by imitating them. [9] stated that the emerging reach of skits in the age of social media has brought about a change in audience media consumption habit, expectation and content production for entertainment. They added also that the audience now have access to global social media platforms where skits all over the world can be viewed, leaving them with unlimited array of entertainment.…”
Section: Skit Makingmentioning
confidence: 99%
“…In the Nigeria entertainment space, several skits have been created by different entertainment personalities and others alike to drive home their point or message.Ojomo and Sodeinde [9] further explained that "Nigerian skit makes have been seen to be active in dedicating certain episodes of their skits to address issues around domestic and sexual violence, cultural values, insecurity, police brutality and COVID-19. Some others they added "are known for theme-based skits and specific comedy styles which provide entertainment on certain identified situations or issues in the society."…”
Section: Skit Makingmentioning
confidence: 99%
“…The past decade has witnessed a digital transformation that has resulted in content production shifting from traditional television (TV) broadcasting to online platforms (García–Perdomo, 2021; S.-H. Yoon et al, 2021). This shift represents a new wave of media globalization, facilitated by online platforms such as YouTube and other social media (Girardin et al, 2020; Ojomo & Sodeinde, 2021), whose ease of access has made the process of content distribution more “frictionless” compared to traditional means like national broadcasting (Cunningham, 2015). These online platforms have also facilitated the monetization of content produced by creators from various cultural backgrounds, enabling them to establish their brands and engage with a wide-ranging, cross-cultural fanbase on a transnational level (Cunningham & Craig, 2016; S.…”
Section: Introductionmentioning
confidence: 99%